FAO Food Loss Index methodology and policy implications - Ulrich Koester; Ekaterina Galaktionova (Studies in Agricultural Economics, 2021)
In 2015, all 193 UN member countries agreed to halve global food losses and waste by the year 2030. In this article, we are going to explore why the first official study on food loss and waste (FLW) by Gustavsson et al. FAO, 2011 cannot be used as a reasonable basis for policymaking – even though it underlies Sustainable Development Goal (SDG) 12.3. Then we will look at the new proposal by the Food and Agriculture Organization of the United Nations (FAO), which aims to harmonise the methodology for FLW research employing the Food Loss Index (FLI). In particular, we are going to assess the suitability of the FLI as a tool for policymaking. We would like to highlight that although both papers have played an important role in raising awareness about the global problem of FLW and in encouraging further research, they do not solve such important issues as providing a unified definition of FLW, the aggregation of heterogeneous commodities within a single category, and the absence of a methodology and data, both of which are certainly needed for policymaking. The objective of the article is to start a discussion about those issues, as even the recent flagship FAO study (2019) openly presents such a dichotomy between on the one hand, the aggregated percentage number of the Food Loss Index and on the other hand, the call for specification and precision in shaping policy measures, based on cost/benefit analyses.
Keywords: Q18; 330; food loss; waste; policy; methodology; SDG